Dynamic stiffness formulation for free orthotropic plates. (23rd June 2015) - Ghorbel, O.; Casimir, J.B.; Hammami, L.; Tawfiq, I.; Haddar, M.
Abstract: This paper presents a procedure for developing the dynamic stiffness matrix of a free orthotropic Kirchhoff plate. The dynamic stiffness matrix is computed for free edge boundary conditions of the plate that allow assembly procedures. The method is based on a strong formulation of Kirchhoff plate equations and series solutions, taking advantage of the symmetry and Gorman type decomposition of the free boundary conditions. The performances of the so-called Dynamic Stiffness Method (DSM) are evaluated by comparing the harmonic responses of an orthotropic Kirchhoff plate with those obtained from the Finite Element Method using four noded quadrilateral elements. Abstract : Highlights: We present a procedure for calculating the dynamic stiffness matrix of free orthotropic pates. Free boundary conditions are required for plate assemblies. Harmonic analysis for two load cases is presented. The numerical validation is achieved thanks to comparisons with FE results.